Aantekeninge by drie klein geskiedenisse - Willemse, Hein (Tydskrif vir Letterkunde, 2010)
The reviewer identifies three disparate texts, Koos Malgas Sculptor of the Owl House (Julia Malgas and Jeni Couzyn, 2008), The Black Countess (R. E. van der Ross, 2008) and Die verhaal van Elandskloof (“The Story of Elandskloof”, Tobie Wiese assisted by Ricky Goedeman, 2009) as counter-discursive texts writtten against specific hegemonic practices. The first text presents a reevaluation of the contribution of Koos Malgas to the famous Outsider Art place, The Owl House in Nieu Bethesda; the second is a short biography on the black countess, Martha Grey and the third is a lay history of a Dutch Reformed Church mission station, Elandskloof. The writer discusses the obvious similarities between these texts such as the co-operation between authors, the margin as a site of resistance, the fragmented documentation of marginalised lives, the formation and re-formation of identities and the tensions around expressions of ‘truth’.